Air Embolism into Superior Mesenteric Artery Following Replacement of Ascending Aorta for Aortic Dissection – A Rare and Fatal Case. Issue 1 (18th October 2018) - Lambert, Lukas; Grus, Tomas; Spunda, Rudolf; Balik, Martin; Trca, Stanislav
We report an unusual case of fatal air embolism into the superior mesenteric artery in a patient, who underwent replacement of the ascending aorta for aortic dissection type A. CT performed twice on the first postoperative day showed abundant air in the superior mesenteric artery and its branches (but not in the portal-venous system) indicating air embolism with no signs of bowel necrosis. On the second postoperative day, the patient underwent extensive bowel resection due to bowel ischemia and died on the third postoperative day on MODS/SIRS.